1998
DOI: 10.1002/(sici)1097-4628(19980328)67:13<2131::aid-app3>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal crosslinking of cis‐1,4‐polybutadiene at ultrahigh pressures

Abstract: cis-1,4-Polybutadiene (BR) samples, in the absence of crosslinking agents, were simultaneously compressed by ultrahigh pressures ( ú4.0 GPa) and annealed between 25 and 180ЊC. The BR samples were crosslinked when the annealing temperatures were above 100ЊC. The Vickers microhardness of the treated BR increased and the extent of swelling decreased rapidly as the annealing temperature increased, indicating that the crosslinking density increased. Solid-state carbon-13 nuclear magnetic resonance and Fourier trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…However, in their work, the cis-trans transition was observed only at an ultrahigh pressure (>4.0 GPa). 43 In this study, the phenomenon of trans-1,4-structure concentration increasing during the cross-linking (165-195 C) does not necessarily mean that trans-1,4-structure does not participate in the cross-linking. It is only revealed that the number of trans-1,4-structure converted from cis-1,4 is much higher than that of participating in the cross-linking reaction.…”
Section: In Situ Ftir Spectroscopymentioning
confidence: 70%
“…However, in their work, the cis-trans transition was observed only at an ultrahigh pressure (>4.0 GPa). 43 In this study, the phenomenon of trans-1,4-structure concentration increasing during the cross-linking (165-195 C) does not necessarily mean that trans-1,4-structure does not participate in the cross-linking. It is only revealed that the number of trans-1,4-structure converted from cis-1,4 is much higher than that of participating in the cross-linking reaction.…”
Section: In Situ Ftir Spectroscopymentioning
confidence: 70%
“…The infrared spectrum of PBD cross-linked under vacuum confirms that isomerization occurs. PBD contains 98% cis-1,4-, with smaller amounts of the trans-1,4-, and 1,2 -vinyl linkages [17] . Cis-1,4-PBD shows a broad strong C-H out-of-plane bending mode at 740 cm −1 , while in trans-1,4-isomer this band is at 965 cm −1 and is much sharper, and the 1, 2-vinyl isomer shows two bands: vinyl CH at 995 and vinyl CH2 at 912 cm −1 [9], [10] .…”
Section: The Effect Of Oxygen On Cross-linkingmentioning
confidence: 99%
“…High pressure cross-linking of PB has been previously studied by ex situ measurements for pressures up to 0.3 GPa at 513 and 523 K, which gave crosslink densities typical of an elastomer, 14 and above 4 GPa in the 373-453 K range, which gave properties ranging from elastic to brittle. 15 By simultaneous high pressure, in situ, measurements it is possible to determine the kinetics of the cross-linking process as well as to observe changes in properties, and to study the effect of both temperature and strong isothermal densification on the polymer properties before and after crosslinking. This is a relatively unexplored method to alter the state of a network polymer and obtain denser forms to augment interactions in pure and filled polymers.…”
Section: Introductionmentioning
confidence: 99%